Green technology design approach for liveable park of Tasik Biru Kundang, Malaysia / Rijal Saffuan, Junaidah Ariffin and Zamreen Amin - Saffuan, Rijal; Ariffin, Junaidah; Amin, Zamreen (Faculty of Architecture, Planning and Surveying, 2013)
Green Technology design approach is a new solution that must be applicable to preserve a nature and reduce the pollution. There are so much innovation could be use to in the development of the park to reduce the electricity use, eco-friendly and liveable for the community. This paper aims to exemplify an effort by a group of students, through multi-professional inputs, in designing for a city facility that can add more towards a liveable city. The results of the approach are multidisciplinary design that includes the idea from multi-professional in making a livable park for community surroundings Tasik Biru Kundang, Kuang, Selangor, Malaysia.